Kehamilan Lebih Dari Tiga Memiliki Pengaruh Besar Terjadinya Perdarahan Pasca Bersalin - Andri Nur Sholihah; Nopija (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Background: Based on data from the Public Health Office of Yogyakarta Special Province in 2014, the cause of Maternal Mortality Rate (MMR) in Yogyakarta was 40 cases. There were 12 cases of maternal death, especially in Sleman, and the causes of maternal death were due to hemorrhage. In Regional Public Hospital of Prambanan, the data presented that during January 2015- December 2017 the cases     of hemorrhage were 71 patients. Methodes. The objective of this study was to determine the correlation between parity and the incidence of pasca bersalin hemorrhage in Regional Public Hospital of Prambanan. This study applied a case control analytic survey method with a retrospective time approach. The samples of the case group were 44 respondents, and the control group were 44 respondents in January 2015 - December 2017 with total sampling technique for the case group and purposive sampling for the control group. The instruments used were the observation sheets and the data analysis used Chi square Result: of Chi square test in the case group of maternal parity at risk of experiencing hemorrhage was as much as 32%, and in the control group of maternal parity who were not at risk of experiencing pasca bersalin hemorrhage was as much as 20%. The p value was 0.001, and the Odds Ratio value (OR) was 4.173. Conclusion : There was a correlation between parity and the incidence of hemorrhage. The high risk maternal parity is 4 times more at risk of experiencing the incidence of pasca bersalin hemorrhage than the maternal parity which is not at risk. It is expected that midwives can improve